SAM II aerosol measurements during the 1989 AASE - Osborn, M. T.; Pitts, M. C.; Powell, K. A.; Mccormick, M. P. (1990)
The Stratospheric Aerosol Measurement II (SAM II) satellite experiment measures 14 daily 1.0-micron aerosol extinction profiles in the high northern latitudes. These SAM II data were used to spot the locations of polar stratospheric clouds (PSCs) and provide an overview of the vertical structure of the upper tropospheric and stratospheric aerosols during the 1989 Airborne Arctic Stratospheric Expedition (AASE). Although SAM II measured a higher than average number of PSCs in January 1989 as compared to the previous 10 years, the number of PSCs sighted during the entire 1989 winter season is only slightly above average. Also discussed is the vertical gradient in aerosol extinction which occurs as the SAM II measurement locations cross the polar vortex.